Loss of Environmental Enrichment Elicits Behavioral and Physiological Dysregulation in Female Rats - Morano, Rachel; Hoskins, Olivia; Smith, Brittany L.; Herman, James P. (Frontiers in Behavioral Neuroscience, 2019)
Chronic stress drives behavioral and physiological changes associated with numerous psychiatric disease states. In rodents, the vast majority of chronic stress models involve imposition of external stressors, whereas in humans stress is often driven by internal cues, commonly associated with a sense of loss. We previously exposed groups of rats to environmental enrichment (EE) for a protracted period (1 month), followed by removal of enrichment (ER), to induce an experience of loss in male rats. ER enhanced immobility in the forced swim test (FST), led to hypothalamic pituitary adrenal (HPA) axis hypoactivity, and caused hyperphagia relative to continuously enriched (EE), single-housed (Scon) and pair-housed (Pcon) groups, most of which were reversible by antidepressant treatment (Smith et al., 2017). Here, we have applied the same approach to study enrichment loss in female rats. Similar to the males, enrichment removal in females led to an increase in the time spent immobile in the FST and increased daytime food intake compared to the single and pair-housed controls. Unlike males, ER females showed decreased sucrose preference, and showed estrus cycle-dependent HPA axis hyperactivity to an acute restraint stress. The increase in passive coping (immobility), anhedonia-like behavior in the sucrose preference test and HPA axis dysregulation suggest that enrichment removal produces a loss phenotype in females that differs from that seen in males, which may be more pronounced in nature.